Transforming Growth Factor–β, Interleukin (IL)–18, and IL-12: Effect on the Clinical Course and Complications of Plasmodium falciparum Malaria - Torre, D.; Speranza, F.; Riley, E.M.; Omer, F.M.; Dodoo, D.; Akanmori, B.D. (Journal of Infectious Diseases, 2003)
To the Editor —We read with interest the recent article by Dodoo et al. [1], and we fully agree with them that secretion of proinflammatory cytokines is essentially to clearance of Plasmodium falciparum malaria. This statement is based mainly on several crucial points: (1) early production of interferon (IFN)–γ, stimulated by induction of interleukin (IL)-12 or IL-18 from macrophages [2, 3]; (2) the correlation of high levels of production of malaria-specific INF-γ and decreased risk of development of fever or of clinical malaria during follow-up [1]; (3) the ability of live parasites—rather than dead parasites—to mount an early INF-γ response to malaria antigens, in conjunction with the ability of either γ/δ T cells or NK cells to respond preferentially to live parasites [4]; and, finally, in severe malaria, (4) suppression of the protective effects of IL-12 and transforming growth factor (TGF)–β [5] Taken together, these findings show that innate immune response—and, in part, adaptive immune response, through increased production of INF-γ—limits the initial reproduction of the parasite and subsequently provokes its elimination [6, 7] In our opinion, resolution of P. falciparum malaria is strictly dependent on a very early and effective activation of macrophages, stimulated by various malaria antigens, to produce and secrete IL-12 and IL-18. In the early phase of the immune response, innate immunity—that is, prompt production of IL-12 along with IL-18—may be able to directly activate NK cells and CD8 T cells to produce INF-γ. In addition, activation of NK cells and T cells by IL-18 and IL-12 is also able to produce tumor necrosis factor (TNF)–α, which cooperates with INF-γ to lead to resolution of malarial infection [8] In a subsequent phase, adaptive immunity, CD8 T cells and γ/δ T cells are critical in the immune response, in that they produce and secrete INF-γ [9, 10]. This adaptive immune response, along with the early immune response, leads to a rapid and effective resolution of malarial infection In severe and complicated P. falciparum malaria, including cerebral malaria, there is a dramatic increase and persistent production of TNF-α, paralleled by decreased production of IL-10 and TGF-β [8, 11]. In contrast, the early activation of IL-18 and IL-12 may be weakened, since there is suppression of the protective effects of these cytokines by TGF-β [5]